It’s adu penalti man!: Understanding the translingual practices of an Indonesian family living in the US - Faishal Zakaria (Universitas Merdeka Malang, 2022)
This study examines the kinds of translingual negotiation strategies practiced by an Indonesian family living in the US. This study involved a father and son, natives of Indonesia, who had been in the US for many years. The father and son usually mix and mesh English, Indonesian, and Javanese when communicating. Two kinds of data were collected; the daily talks between the father and son were audiotaped, and follow-up interviews with the father and member checking were used to triangulate the data. The data reveals that the father and son indeed practiced Canagajarah’s (2013b) four translingual negotiation strategies: invoicing, recontextualization, interactional, and entextualization. Additionally, the interview reveals some of the father’s goals with his son’s language learning and literacy in their mother tongue. DOI: 10.26905/enjourme.v7i2.8990